Hydroxyapatite-ciprofloxacin delivery system: Synthesis, characterisation and antibacterial activity - Ciocilteu Maria-Viorica; Mocanu Andreea Gabriela; Mocanu Adriana; Ducu Catalin; Nicolaescu Oana Elena; Manda Valentin Costel; Turcu-Stiolica Adina; Nicolicescu Claudiu; Melinte Razvan; Balasoiu Maria; Croitoru Octavian; Neamtu Johny (Acta Pharmaceutica)
The main objective of this study was to synthesize hydroxyapatite-ciprofloxacin composites using a chemical precipitation method and to evaluate the properties and in vitro release profile of the drug from the hydroxyapatite-ciprofloxacin composites. Composite characterization was achieved by FT-IR, XRD and DLS. Ciprofloxacin determination was accomplished by HPLC, resulting in good incorporation efficiency of the drug (18.13 %). The in vitro release study (Higuchi model C = K t1/2 and Ritger-Peppas model, C = K t0.6) showed a diffusion-controlled mechanism. The antibacterial activity showed that the bacterial growth inhibition zones were approximately equal for the synthesis composites and for the mechanical mixture on the Staphylococcus aureus germ.